Operational effectiveness of blended e-learning program for nursing research ethics. (June 2014) - Cho, Kap-Chul; Shin, Gisoo
Background: Since 2006, the Korean Ministry of Education, Science and Technology, and the National Research Foundation of Korea have taken the lead in developing an institutional guideline for research ethics. Objectives: The purpose was to identify the effectiveness of the Good Research Practice program, developed on a fund granted by the National Research Foundation of Korea, for nurses and nursing students whose knowledge and perception of research ethics were compared before and after the implementation of the Good Research Practice program. Research design: This study was conducted to compare the levels of knowledge and perception of research ethics in the participants before and after the program was implemented. Participant and research context: The participants included 45 nurses and 69 nursing students from hospitals, colleges of nursing, and the Korean Nurses Association, located in Seoul, Korea. Ethical considerations: This study was approved by the Institutional Research Board in Korea. Findings: Based on the Analysis, Design, Development, Implementation, and Evaluation model, the Good Research Practice program was made up of a total of 30 h of the blended learning both online and off-line. The results of this study showed that there were statistically significant differences in both knowledge and perception of research ethics in nursing students and nurses before and after the program had been implemented. Discussion: The concepts of professional nursing ethics, moral issues, and bioethics were often confused with one another and not clearly defined. Therefore, the concept and scope of bioethics, moral judgment, and overall nursing ethics should be well defined and conceptualized in the future. Conclusions: This study suggested integrating research ethics education in the nursing curriculum as a required course of study for nursing students and as part of the in-service training program for nurses in order to improve research ethics in nursing research in Korea.